Ten years of the Inventory of Family Integration (IFI) - Arias Gallegos, Walter L (2024)
Background:  In Peru, various instruments have been validated to evaluate variables associated with the family, but until recently there was no psychological test aimed at evaluating the family that had been created in the country. This study presents the psychometric development and applications of the Inventory of Family Integration (IFI) after ten years of construction, and this being the first and only instrument created in Peru that evaluates the family. Method: This research is a theoretical study. Results: It starts first from the review of the theoretical assumptions on which the instrument rests based on the construct of family integration that is inspired by the systemic family approach. Then, the studies carried out on the psychometric properties of the IFI are presented in chronological order, from its construction in 2013 to the recently published dyadic analysis in fathers and mothers. Finally, the planning of future psychometric research with this instrument is explained in a new stage of applied explorations in the field of psychometrics and the family, both nationally and internationally. Conclusions: The IFI has proven to be a robust and consistent instrument for assessing family integration, but its psychometric properties still need to be evaluated at national and international levels.